Assessing the effect of organizational resilience on economic sustainability of selected SME restaurants in Makati City, Philippines - Abalos, Jed Seraphim C. (Animo Repository, 2022)
Business ventures and entrepreneurial activities significantly impact the country’s economic growth. However, due to the COVID-19 pandemic, businesses under the accommodation and service sector sustained the highest economic losses as the mobilization of resources, operations, and supply chains were limited. The study focuses on how factors of organizational resilience, namely: crisis anticipation, sense making, problem solving and learning affect economic sustainability of small and medium-sized restaurants. The study aims to identify different coping, resilience, and sustainability actions which may be useful to restaurants in developing their coping capabilities and crisis plans to achieve economic sustainability. The study narrows down the scope to selected restaurants located in Makati, Philippines. A total of 100 respondents were gathered coming from SME restaurants located in Makati City, Philippines. The survey questionnaire was made through Google forms and distributed by the researchers online. The researchers also conducted two interviews, wherein one respondent was able to retain its employees during the whole duration of the pandemic while the other respondent had to lay off some restaurant employees as a result of the lockdowns. Pearson Correlation Method, Linear Regression, and Multiple Regression were used to analyze the quantitative data. Pattern Matching was also used to compare and contrast the results of the qualitative information from interviews with the quantitative survey data. The simple linear regression analysis showed that each of the variables has a significant relationship with the economic sustainability of restaurants by testing at a .05 significance level. The multiple regression model also showed the same results by producing a p-value of less than 0.05. It was also observed that Crisis Anticipation had the highest strong positive significant relationship with economic sustainability with an R-value greater than 0.7 compared to the other variables that had R-values less than 0.7. Pattern Matching also supplemented the data shown from the quantitative data and presented how each variable affects the restaurant's economic sustainability. Based on both quantitative and qualitative analysis, it can be gleaned that organizational resilience, covering the variables Crisis Anticipation, Sense making, Problem Solving and Learning significantly affect Economic Sustainability.